2021
DOI: 10.3390/jcm10163537
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhoids Embolization: State of the Art and Future Directions

Abstract: Hemorrhoidal disease is a frustrating problem that has a relevant impact on patients’ psychological, social, and physical well-being. Recently, endovascular embolization of hemorrhoids has emerged as a promising mini-invasive solution with respect to surgical treatment. The purpose of this article is to review the indications, technical aspects, clinical outcomes, and future prospective of endovascular embolization of symptomatic hemorrhoid patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
(66 reference statements)
1
12
0
Order By: Relevance
“…In our series, the technical success rate was 100%, with a 14.2% rate of minor complications according to the classification of the Society of Interventional Radiology [ 21 ]. There were no major complications, finding consistent with that reported in recent publications in the medical literature [ 11 , 16 , 17 , 18 , 24 , 42 , 43 , 44 ]. However, recently, Eberspacher Ch [ 45 ] reported a case study of rectal sigmoid ischemia secondary to hemorrhoidal microparticle embolization in a 58-year-old patient.…”
Section: Discussionsupporting
confidence: 91%
“…In our series, the technical success rate was 100%, with a 14.2% rate of minor complications according to the classification of the Society of Interventional Radiology [ 21 ]. There were no major complications, finding consistent with that reported in recent publications in the medical literature [ 11 , 16 , 17 , 18 , 24 , 42 , 43 , 44 ]. However, recently, Eberspacher Ch [ 45 ] reported a case study of rectal sigmoid ischemia secondary to hemorrhoidal microparticle embolization in a 58-year-old patient.…”
Section: Discussionsupporting
confidence: 91%
“…multifactorial [9]. To understand hemorrhoid disease and best determine the approach to its treatment, we must consider the physiology of the rectum and hemorrhoidal vascularization [1]. Corpus cavernosum recti (CCR) constitutes the functional unit of hemorrhoids [10].…”
Section: Anatomical Importance Of Rectal Arteriesmentioning
confidence: 99%
“…Hemorrhoidal disease (HD) is the most common anorectal disease, with a reported prevalence of 4.4-39.0% depending on various variables [1,2]. The age group with the highest incidence is between the ages of 45-65 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Early proponents of the angiogenesis theory believed that hemorrhoid tissues originated from cavernous tissues, but it was later found that hemorrhoid vessels were not true cavernous bodies ( Rebonato et al, 2021 ; Yang et al, 2022 ; Palumbo et al, 2023 ). Subsequent studies discovered new vessels in hemorrhoid tissues.…”
Section: Inhibiting Angiogenesis To Delay the Development Of Hemorrhoidsmentioning
confidence: 99%